Taurine promotes the rapid recovery of clams (Ruditapes philippinarum) after aerial exposure through the glutathione pathway and by inhibiting apoptosis - Zheng Zhilong; Chen Yimeng; Huang Kaiyue; Li Dongdong; Gao Zhiying; Yan Xiwu; Huo Zhongming; Qin Yanjie (Aquaculture Reports)
As an intertidal species, clams (Ruditapes philippinarum) are constantly exposed to aerial exposure followed by reoxygenation. The antioxidant and apoptosis characteristics during these two phases and the effects of taurine during re-immersion were studied. The clams were exposed to air for 48 h and then re-immersed either in natural seawater (control) or seawater containing 5 µg/mL taurine for 72 h. During re-immersion, an upward trend in mortality rates occurred. Mortality rates of clams in taurine were significantly lower at 24 and 48 h of re-immersion (P < 0.05). The apoptosis rate of the control increased significantly at 48 and 72 h of reoxygenation (P < 0.05), but no obvious changes were observed in the taurine group. Gpx activity was significantly induced by air exposure and significantly high levels were maintained in the taurine group during the whole re-immersion compared to the control. The BAX/BCL-2 ratio in the taurine group was significantly lower than in the control at 48 h of re-immersion. The glutathione pathway (including GSH and Gpx) may play important roles in clams after aerial exposure and reoxygenation, although there are significant increases in mortality and apoptosis rates. Taurine can inhibit apoptosis and reduce mortality mainly through enhancing GSH content, Gpx activity, and BCL-2 expression level during reoxygenation. Consequently, taurine is an ideal additive for the rapid recovery of clams after aerial exposure.